Economic Conditions of a State's Failure - Totleben, Bartosz (Studia Oeconomica Posnaniensia, 2017)
In the article the author has made an attempt to examine the impact of selected economic indicators on the probability of a state's failure. The concept of a state and its failure is introduced at the beginning, followed by a presentation of some failed states over the last few years. In the next part, using the Cox model, an analysis of the impact of five economic variables (initial and average level of GDP per capita, average level of economic growth, inflation rate and resource curse) on the probability of a state's failure was performed. The analysis covers states established in 1960 and afterwards. It was proven that GDP per capita and average economic growth significantly influences the likelihood of failure.